Intraoperative Adverse Event Reporting in Gastrointestinal Cancer Surgery: A Narrative Review on the Application of ClassIntra - Nargis Maqbool; saleema Begum; Muhammad Rizwan Khan (Journal of the Pakistan Medical Association, 2026)
Intraoperative adverse events are inevitable during complex gastrointestinal cancer surgeries, ranging from minor technical issues to life-threatening complications. Their impact on patient outcomes underscores the need for standardised reporting as no universally accepted system currently exists. The ClassIntra classification system is a five-tier severity scale based on the required interventions, mirroring the Clavien-Dindo Classification for postoperative complications. The current narrative review was planned to explore current intraoperative adverse event reporting practices in gastrointestinal cancer surgery, and to evaluate the effectiveness of ClassIntra in enhancing accuracy and consistency. Validation studies in gastric, colorectal and hepatopancreaticobiliary surgeries demonstrate its predictive value for postoperative complications and surgical outcomes. Although data specific to gastrointestinal oncology remains limited, initial evidence has shown ClassIntra’s potential as a standardised tool. A collaborative effort is essential for its widespread adoption, fostering improved safety and outcomes in gastrointestinal cancer surgeries through routine intraoperative adverse event documentation and feedback. Keywords: Intraoperative adverse events, ClassIntra, Adverse event reporting, Gastrointestinal cancer surgery.